Different characteristics of bloodstream infection during venoarterial and venovenous extracorporeal membrane oxygenation in adult patients - Hyoung Soo Kim (Nature Portfolio, 2021)
Abstract Currently, there is scarcity of data on whether differences exist in clinical characteristics and outcomes of bloodstream infection (BSI) between venoarterial (VA) and venovenous (VV) extracorporeal membrane oxygenation (ECMO) and whether they differ between Candida BSI and bacteremia in adult ECMO patients. We retrospectively reviewed data of patients who required ECMO for > 48 h and had BSIs while receiving ECMO between January 2015 and June 2020. Cases with a positive blood culture result within 24 h of ECMO implantation were excluded. We identified 94 (from 64 of 194 patients) and 38 (from 17 of 56 patients) BSI episodes under VA and VV ECMO, respectively. Fifty nine BSIs of VA ECMO (59/94, 62.8%) occurred in the first 2 weeks after ECMO implantation, whereas 24 BSIs of VV ECMO (24/38, 63.2%) occurred after 3 weeks of ECMO implantation. Gram-negative bacteremia (39/59, 66.1%) and gram-positive bacteremia (10/24, 41.7%) were the most commonly identified BSI types in the first 2 weeks after VA ECMO implantation and after 3 weeks of VV implantation, respectively. Timing of Candida BSI was early (6/11, 54.5% during the first 2 weeks) in VA ECMO and late (6/9, 66.7% after 3 weeks of initiation) in VV ECMO. Compared with bacteremia, Candida BSI showed no differences in clinical characteristics and outcomes during VA and VV ECMO, except the significant association with prior exposure to carbapenem in VA ECMO (vs. gram-negative bacteremia [P = 0.006], vs. gram-positive bacteremia [P = 0.03]). Our results suggest that ECMO modes may affect BSI clinical features and timing. In particular, Candida BSI occurrence during the early course of VA ECMO is not uncommon, especially in patients with prior carbapenem exposure; however, it usually occurs during the prolonged course of VV ECMO. Consequently, routine blood culture surveillance and empiric antifungal therapy might be warranted in targeted populations of adult ECMO patients, regardless of levels of inflammatory markers and severity scores.